2013
DOI: 10.7860/jcdr/2013/6565.3763
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Knowledge, Attitude and Practices on Immunization of Children in Urban Slums of Bijapur City, Karnataka

Abstract: Background: The immunization coverage is not uniform in India. In Karnataka, except for Uttar Kannada District (very high immunization coverage of 95%) and 14 districts that have shown a better immunization coverage (>85% coverage), the remaining 15 districts (including Bijapur District) have poor coverage. The United Nations Children's Fund (UNICEF) 2002 report on Bijapur district shows that only a little over one fourth of the children were fully immunized (25.8%). The state's fully vaccinated figure was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
57
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 2 publications
18
57
1
Order By: Relevance
“…75.3% of them said they were aware of the diseases which were prevented by the vaccines given in the UIP. This is in contrast to the findings of other studies; Angadi et al, Manjunath et al 10,15 This may be because of regular health education programmes attended by mothers which were organized by anganwadi workers/Asha workers. Attending the health education meetings was found to be associated with Immunization status of the child, though it was not a significant independent predictor for immunization status ( 14,16 Further the main reason behind partial immunization was found to be lack of information regarding when to return for 2 nd and 3 rd vaccination followed by lack of motivation and inconvenient time of immunization respectively (Table 1).…”
Section: Immunization Status Of Children and Reasons Of Partial Immuncontrasting
confidence: 56%
See 2 more Smart Citations
“…75.3% of them said they were aware of the diseases which were prevented by the vaccines given in the UIP. This is in contrast to the findings of other studies; Angadi et al, Manjunath et al 10,15 This may be because of regular health education programmes attended by mothers which were organized by anganwadi workers/Asha workers. Attending the health education meetings was found to be associated with Immunization status of the child, though it was not a significant independent predictor for immunization status ( 14,16 Further the main reason behind partial immunization was found to be lack of information regarding when to return for 2 nd and 3 rd vaccination followed by lack of motivation and inconvenient time of immunization respectively (Table 1).…”
Section: Immunization Status Of Children and Reasons Of Partial Immuncontrasting
confidence: 56%
“…Angadi et al, Kadri et al also observed the similar trend. 10,13 In the present study, it was found that immunization status was not associated with factors such as education of mother and socio-economic status of the family. This was in contrast to the findings of study done by Bholanath et al, that found that maternal education and socioeconomic status were significant independent predictors of immunization status.…”
Section: Immunization Status Of Children and Reasons Of Partial Immunmentioning
confidence: 67%
See 1 more Smart Citation
“…This shows that the knowledge of government healthcare workers is better than the private workers about the vaccination at birth. It was concluded in a study done in Bijapur city that the main reason for partial as well as non-immunization was a lack of information among health workers and lack of motivation to the mother [13]. The motivation to vaccinate the children needs to be spread primarily through the health workers.…”
Section: Pandiamunian and Ishwaryamentioning
confidence: 99%
“…The Content validity index of the scale (S-CVI) was also measured based on the rating by the experts. 8,[9][10][11][12][13][14][15][16][17][18][19] The statistical analysis was done using Microsoft Excel and the Statistical Package for Social Science (SPSS) version 22 for windows. Cronbach's alpha was used to estimate the internal consistency/ reliability of the questions in the questionnaire.…”
Section: Validation Of the Questionnairementioning
confidence: 99%